2015
DOI: 10.1136/gutjnl-2014-307030
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-deficient diet promotes colitis and SIRT1-mediated endoplasmic reticulum stress

Abstract: SIRT1 is a master regulator of ER stress and severity of experimental colitis in case of MDD. It could deserve further interest as a therapeutic target of IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 49 publications
3
43
0
2
Order By: Relevance
“…The differential alterations of these gut microorganisms in these two studies may directly lead to distinct responses of SIRT1 iKO mice to DSS-induced colitis. Nevertheless, our observations in the present study are consistent with previous reports that reduced SIRT1 expression, inhibition of SIRT1 activity, or a SIRT1 mutation that decreases its activity, is associated with intestinal inflammation and colitis in both humans and rodents, whereas activation of SIRT1 by resveratrol, Cay10591, or SRT1720 prevents and cures experimental colitis 9-12 . Our findings provide a direct link between SIRT1, gut microbiota, and intestinal inflammation, and highlight the therapeutic potential of SIRT1-activating compounds in the treatment of human IBD.…”
Section: Discussionsupporting
confidence: 93%
“…The differential alterations of these gut microorganisms in these two studies may directly lead to distinct responses of SIRT1 iKO mice to DSS-induced colitis. Nevertheless, our observations in the present study are consistent with previous reports that reduced SIRT1 expression, inhibition of SIRT1 activity, or a SIRT1 mutation that decreases its activity, is associated with intestinal inflammation and colitis in both humans and rodents, whereas activation of SIRT1 by resveratrol, Cay10591, or SRT1720 prevents and cures experimental colitis 9-12 . Our findings provide a direct link between SIRT1, gut microbiota, and intestinal inflammation, and highlight the therapeutic potential of SIRT1-activating compounds in the treatment of human IBD.…”
Section: Discussionsupporting
confidence: 93%
“…Considering that ELAVL1/HuR export is also altered in patient fibroblasts and in hippocampal neurons of the Cd320 KO mice (the experimental systems without the presence of G418), we conclude that cellular response to stress mediated by ELAVL1/HuR-containing hnRNP complex shuttling is impaired in both human and mouse under aberrant Cbl metabolism. Together with the previous evidence that in TO and OT model cell system, cellular Cbl deficit produced non-adapted unfolded protein response due to decreased SIRT1 activity (5,13,31), our data here provide a mechanistic link between anti-stress responses mediated by ELAVL1/HuR and SIRT1 activity. A major consequence of ELAVL1/HuR nuclear retention is the confinement of ELAVL1/HuR target mRNAs like Sirt1 in the nucleus, hence reduced translation of ELAVL1/HuR-relevant stress response proteins.…”
Section: Discussionsupporting
confidence: 84%
“…A major consequence of ELAVL1/HuR nuclear retention is the confinement of ELAVL1/HuR target mRNAs like Sirt1 in the nucleus, hence reduced translation of ELAVL1/HuR-relevant stress response proteins. A decreased expression and activity of SIRT1 is a key component of the non-adapted response to the ER stress of the TO cells and the rats subjected to Cbl and folate deficient diet (5,12,13,31), as reduced SIRT1 protein expression leads to HSF1 hyperacetylation, the latter in turn reduces the expression of heat shock proteins (HSPs) (32). Besides HSPs, other gene function may also be affected as decreased SIRT1activity can contribute to dysregulated nuclear receptor co-regulation via deacetylated PGC1α, as observed in the brain, heart and gut of rats deficient in Cbl and folate (10–14,31).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of SIRT1 by resveratrol, NAD+, or calorie restriction could attenuate ER stress via the PERK/eIF2α, ATF6/CHOP, or IRE1α/ JNK-mediated pathways. [52][53][54][55][56] In this study, we observed the downregulation of SIRT1 in macrophages treated with both TiPs and CoPs, and the treatment of resveratrol showed a similar effect on the inflammatory response with an ER stress inhibitor. Those results suggest a correlation between ER stress and SIRT1 in the pathological process of aseptic loosening.…”
mentioning
confidence: 63%